Pakistan Development Update, April 2016 : From Stability to Prosperity - World Bank Group (World Bank, Washington, DC, 2016)
South Asia emerged as the fastest growing region in the world in 2015, posting GDP growth of 7 percent. Weak oil and commodity prices, slowing capital flows and shrinking global trade contributed towards a deceleration of growth in most of the world's economies. South Asia - as a net importer of oil - was an anomaly, growing significantly on the back of higher private consumption and public investment. Higher remittances and reserve buffers throughout the region offset the fall in exports caused by the drop in global demand. The region is set to maintain real GDP growth above 7 percent over the next few years. However, the tailwinds are now fading - capital flows have declined and remittances are starting to feel the reality of low oil prices. Pakistan, while not growing as quickly as its neighbors, has continued its steady growth recovery in H1FY16. Strong growth in consumption, rising foreign exchange reserves, fast-growing workers' remittances and a lower import bill compensated for a significant fall in exports. Low oil prices generated a significant boost, driving a 9.1 percent fall in the import bill and reducing inflation significantly, in turn creating scope to reduce the policy rate. Private sector consumption, propelled by higher remittances and a loosened monetary policy, is expected to account for over half of FY16 GDP growth.